A Role of Udumbara Ksheer Sutra in Ano Rectal Fistula: An Ayurvedic Review (International Journal of Ayurveda and Pharma Research, 2022)
Acharya Sushrut has involved Bhagandara among the Ashtamahagad (8 dreadful diseases). At first it is present as Pidika (boil/abscess) in Apakwa (non-suppurated) state, become Bhagandara when it becomes Pakwa (suppurated). As defined in modern science, it is associated with fistula in ano. An anal fistula is an abnormal track having an external opening in the perianal region and internal opening in the anal canal and/or rectum.Ayurveda has a special approach to fistula management. All anal fistulas counter well to different forms of Kshar and Ksheer Sutra therapy. They are nothing but the medicated seton. The Ksheer sutra mechanical and chemical action of drugs coated on the thread work jointly to cut, cure, drain and clean the fistulous tract, thereby promoting track/wound healing. Though Bhrihattrayi, (chief three texts of Ayurveda) stated the use of Kshar Sutra, there is no proper description of their method of preparation. In eleventh century, Chakrapani Datta mentioned the preparation method of Ksheer sutra in his book Chakradatta for the first time which is indicated in Arsha and Bhagandara.Apamarga Kshar Sutra is the standard Kshar Sutra, and but it has some disadvantages. A variety of other Kshar Sutra, as well as Ksheer Sutra, have been prepared to resolve these inconveniences of Apamarga Kshar Sutra. One of them is Udumbara Ksheer Sutra which was founded by Prof. P.J Deshpande and M.K Jalan in 1984. Udumbara is one among the Nyagradhadi Gana Dravya mentioned by Acharya Sushrut. He described in Bhagandara Chikitsa that the Nyagradhadi Gana Dravyas are Bhagandaranashak.